2020
DOI: 10.1177/1078155220948943
|View full text |Cite
|
Sign up to set email alerts
|

Suggestion of Tunisia’s medical oncologist in the management of breast cancer during COVID-19 pandemic

Abstract: Cancer patients are at higher risk to be infected with COVID-19 and to develop a more severe form. Breast cancer (BC) treatments, including chemotherapy (CT), targeted therapy and immunotherapy can weaken the immune system and possibly cause lung problems. For all these reasons Salah Azaiez Institute's department of Medical Oncology took drastic actions to protect patients. In this article we will discuss protocol adjustments taken during the COVID-19 pandemic for breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
4
0
4
Order By: Relevance
“…Endocrine treatments [tamoxifen, aromatase inhibitors, and luteinizing hormone-releasing hormone (LHRH) agonist] were continued during the COVID-19 pandemic since they do not affect the immune system ( 55 ). In terms of radiotherapy, Leonardi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocrine treatments [tamoxifen, aromatase inhibitors, and luteinizing hormone-releasing hormone (LHRH) agonist] were continued during the COVID-19 pandemic since they do not affect the immune system ( 55 ). In terms of radiotherapy, Leonardi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine treatments [tamoxifen, aromatase inhibitors, and luteinizing hormone-releasing hormone (LHRH) agonist] were continued during the COVID-19 pandemic since they do not affect the immune system (55). In terms of radiotherapy, Leonardi et al reported that there was no significant difference in the time interval between treatments and radiotherapy for high-risk patients (56).…”
Section: Cluster 4: Diagnosis and Treatment Of Breast Cancer Patients...mentioning
confidence: 99%
“…São fornecidos medicamentos por dois ou três ciclos, avaliando por teleconsulta a condição clínica e exames laboratoriais. Já paraYahyaoui et al (2020), todos os tratamentos já iniciados devem ser completados com o regime anteriormente estabelecido.De acordo com o estudo deDave et al (2021), treze dos 3776 pacientes com HER2+, com idade média de 73, não tiveram terapia com anti-HER2 ou quimioterapia quando o manejo padrão os teria incluído. Outras características desse grupo era: baixo estágio do tumor (T1 = 5/13, T2 = 7/13), baixo estágio nodal (N0/N1 = 11/13) e doença amplamente ER+ (11/13).…”
unclassified
“…Além disso, nenhuma mudança é relatada na administração de terapia de manutenção com anti-Her2. Já em relação aos idosos com MBC, 80% dos entrevistados consideraram apropriado suspender a quimioterapia durante a pandemia.ParaBrown et al (2020) eViale et al (2020), as terapias orais devem ser preferidas sempre que possível, como se vê no estudode Fedele et al (2020), em que 56% dos médicos prescreveram quimioterapia oral para reduzir o acesso ao hospital.Concomitantemente, 55% deles preferiram monoquimioterapia em vez de poliquimioterapia para reduzir o risco de imunossupressão, sendo que capecitabana e vinorelbina são boas alternativas(Brown et al, 2020) Yahyaoui et al (2020). considerou a quimioterapia oral para MBC como quarta linha de tratamento.…”
unclassified
See 1 more Smart Citation